Differences in verbal and nonverbal IQ test scores in children with autism spectrum disorder. (May 2018) - Grondhuis, Sabrina N.; Lecavalier, Luc; Arnold, L. Eugene; Handen, Benjamin L.; Scahill, Lawrence; McDougle, Christopher J.; Aman, Michael G.
Highlights: Intelligence tests are an important part of diagnostic assessments for children with suspected ASD. IQ tests appear to be equivalent and interchangeable in typically developing children, but may not be in children with ASD. This study compared a verbal measure of intelligence and a nonverbal measure of intelligence. In children with ASD these IQ tests often elicit different results that may influence clinical interpretation. Abstract: Background: Intelligence tests are a fundamental component of diagnostic assessments for children with suspected autism spectrum disorder (ASD). There are many assessments available, but scores across tests may not be comparable in children with ASD. Method: Eighty children (68 boys) age 4–14 years with ASD completed the Stanford-Binet Intelligence Scales, 5th Edition (SB5), a verbal measure of intelligence, and the Leiter International Performance Scale – Revised (Leiter-R), a nonverbal measure of intelligence. Results: Although discrepancies went in both directions, we found significantly higher mean scores on the Leiter-R than SB5 (9.6 point difference). Children younger than 8 years had more pronounced discrepancies (13.8 points vs. 3.5 points for >8 years), and children with less-developed language skills had greater discrepancies (13.1 points vs. 5.8 points for higher language skills). Conclusion: This suggests these IQ tests are not interchangeable and language demands may produce different results that could impact clinician interpretation. Both clinicians and researchers should be aware of the likely impact of adopting primarily verbal vs. nonverbal tests when assessing children with ASD, especially those with less language.